2021
DOI: 10.1038/s41598-021-92706-x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Lactuca serriola seeds contain endophytic bacteria that contribute to drought tolerance

Abstract: The mutualistic relationship between alien plant species and microorganisms is proposed to facilitate or hinder invasive success, depending on whether plants can form novel associations with microorganisms in the introduced habitats. However, this hypothesis has not considered seed endophytes that would move together with plant propagules. Little information is available on the seed endophytic bacteria of invasive species and their effects on plant performance. We isolated the seed endophytic bacteria of a xer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…In this study, KAS1 was found to be the most dominant isolate since it was most frequently isolated from seeds of millet followed by KAS4 ( Table 1 ). Recently, a study reported the occurrence of Kosakonia cowanii as the most common SEB in seeds of Lactuca serriola ( Jeong et al, 2021 ). Pantoea and Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, KAS1 was found to be the most dominant isolate since it was most frequently isolated from seeds of millet followed by KAS4 ( Table 1 ). Recently, a study reported the occurrence of Kosakonia cowanii as the most common SEB in seeds of Lactuca serriola ( Jeong et al, 2021 ). Pantoea and Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In both trials, we found that isolates KAS1, and KAS4 significantly increased the root-shoot lengths, biomass, and photosynthetic pigments in seedlings, and both isolates were the highest producers of IAA and the best P solubilizers ( Table 2 ). Kosakonia cowanii and Pantoea species have been reported as seed vectored bacteria in many crop seeds with plant-growth promoting activities ( Chimwamurombe et al, 2016 ; Verma et al, 2017 ; Jeong et al, 2021 ). The profound effect of KAS1 and KAS4 treatment on root architecture development of seedlings may be because of their IAA activities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Khalaf et al [22] reported that Bacillus and Paenibacillus isolated from cucurbit seeds emit volatile organic compounds (VOCs) and secrete extracellular ribonucleases which could suppress fungal pathogens. Jeong et al [23] observed that the colonization of seed endophytic bacterium Kosakonia cowanii GG1 into Arabidopsis thaliana resulted in the stimulation of plant growth under drought conditions. Xu et al [24] found a seed-borne Bacillus strain that improved the root and shoot growth of tomato, probably through the production of ACC deaminase and nitrogen fixation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ecological significance of SEB in weedy species has gained attention just recently. For instance, SEB can contribute to the seed germination and growth in invasive Phragmites australis (White et al, 2018 ), drought resistance in Lactuca serriola (Jeong et al, 2021 ), and the competitive ability by antagonistic effects on the competitor species (Elmore et al, 2019 ). Although soil microbiome has been postulated as a major source of mutualistic microorganisms for weedy plant species (Trognitz et al, 2016 ), our results imply that SEB might be another source of mutualistic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their plausible ecological significance (Elmore et al, 2019 ; Jeong et al, 2021 ; White et al, 2018 ), relatively little information is available on the characteristics of SEB in weed plant species. Most information on the SEB has come from studies using agriculturally important crop plants (Card et al, 2015 ; Pal et al, 2019 ; Shahzad et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%